Optimal home purchase age and its determinants : a quantitative analysis - Lau, Chzee An (2017)
In view of the significant impacts of housing on both the individual utility and the macroeconomy, we formulate a dynamic life-cycle model that prescribes housing as a discrete choice variable to study the optimal age for individuals to purchase their first home and the various factors that influence this age. We first show that our results are coherent with actual historical economic events to demonstrate the validity of our model. In addition, we also perform a simulation to realistically evaluate how the optimal home purchase age will react to shocks in income, housing prices and housing utility. In general, adverse shocks induce individuals to defer their home purchases and allocate more towards non-housing consumption. However, the degree of response differs between anticipated and unanticipated shocks. When a shock is unanticipated, individuals only adjust their consumption patterns at the period the shock occurs. As a consequence, individuals sub-optimally under- or over-postpone their home purchase age as compared to the case of an anticipated shock. From our sensitivity analysis, we identify the determinants of the optimal home purchase age to be income, housing price and housing utility. In our cross-country comparison, it is found that houses are more valued in China than in the US. This observation may be attributed to their native cultural beliefs that housing will boost their social standing and that a house purchase should precede marriage.